A Systematic Review and Meta-Analysis on Short-Term Particulate Matter Exposure and Chronic Obstructive Pulmonary Disease Hospitalizations in China. Issue 4 (April 2019) - Wang, Kan; Hao, Yanhui; Au, William; Christiani, David C.; Xia, Zhao-Lin
Abstract : Objective: We conducted a meta-analysis of short-term particulate matter (PM) exposure and chronic obstructive pulmonary disease (COPD) hospitalizations in China, including data from two-pollutant model. Methods: From PubMed and Web of Science, we selected case-crossover or time-series studies conducted in Mainland China, Hong Kong, Macao, or Taiwan to investigate the association between PM exposure and COPD hospitalizations. The meta-analysis was performed using data from both single-pollutant and two-pollutant models for PM2.5 and PM10 . Results: A total of 16 studies were included in our analysis. Short-term exposure to PM2.5 and PM10 were both significantly associated with COPD hospitalizations. The results remained robust in two-pollutant model, whereas subgroup analyses demonstrated a modest heterogeneity. Conclusions: Our review shows a small but obvious exposure-hospitalization effect in China. More studies are needed to generate the needed evidence, and advocacy is needed to stimulate initiation of solutions to the problem.